Beispiel Nr: 01
$ \text{Gegeben:} \\ a1 \cdot x + b1\cdot y + c1\cdot z=d1\\ a2\cdot x + b2\cdot y + c2\cdot z=d2\\ a3\cdot x + b3\cdot y + c3\cdot z=d3\\ \\ \text{Gesucht:} \\\text{x,y,z} \\ \\ \textbf{Gegeben:} \\ 11 x +13 + 4 z=37\\ 12 x +14 y + 5 z=40\\ 9 x +3 y + 3 z=15\\ \\ \\ \textbf{Rechnung:} \\ 11 x + 13 y + 4 z=37\\ 12 x +14 y +5 z=40\\ 9 x +3 y +3 z=15\\ D_h=\left|\begin{array}{ccc} 11\ & 13 & 4\\ 12&14 & 5\\ 9& 3 & 3 \\ \end{array}\right| \begin{array}{cc} 11\ & 13 \\ 12&14 \\ 9& 3 \end{array} \\ D_h=11 \cdot 14 \cdot 3+13 \cdot 5 \cdot 9 +4 \cdot 12 \cdot 3 - 4 \cdot 14 \cdot 9 -11 \cdot 5 \cdot 3 -13 \cdot 12 \cdot 3=54 \\ D_x=\left|\begin{array}{ccc} 37\ & 13 & 4\\ 40&14 & 5\\ 15& 3 & 3 \\ \end{array}\right| \begin{array}{cc} 37\ & 13 \\ 40&14 \\ 15& 3 \end{array} \\ D_x=37 \cdot 14 \cdot 3+ 13 \cdot 5 \cdot 15 +4 \cdot 40 \cdot 3 - 4 \cdot 14 \cdot 15 - 37 \cdot 5 \cdot 3 -13 \cdot 40 \cdot 3=54\\ D_y=\left|\begin{array}{ccc} 11\ & 37 & 4\\ 12&40 & 5\\ 9& 15 & 3 \\ \end{array}\right| \begin{array}{cc} 11\ & 37 \\ 12&40 \\ 9& 15 \end{array} \\ D_y=11 \cdot 40 \cdot 3+37 \cdot 5 \cdot 9 +4 \cdot 12 \cdot 15 - 4 \cdot 40 \cdot 9 -11 \cdot 5 \cdot 15 -37 \cdot 12 \cdot 3=108 \\ D_z=\left|\begin{array}{ccc} 11\ & 13 & 37\\ 12&14 & 40\\ 9& 3 & 15 \\ \end{array}\right| \begin{array}{cc} 11\ & 13 \\ 12&14 \\ 9& 3 \end{array} \\ D_z=11 \cdot 14 \cdot 15+13 \cdot 40 \cdot 9 +37 \cdot 12 \cdot 3 - 37 \cdot 14 \cdot 9 -11 \cdot 40 \cdot 3 -13 \cdot 12 \cdot 15=0\\ x=\frac{54}{54} \\ x=1 \\ y=\frac{108}{54} \\ y=2 \\ z=\frac{0}{54} \\ z=0\\ L=\{1/2/0\} $